Annual Plan 2000-2001 Volume-I Government of Karnataka - Planning Commission (Planning Commission, 2000)
The budgeted outlay for the Annual Plan 2000-2001 is Rs.7274 crores. The budgeted outlay represents an increase of 39 per cent over the revised outlay of 1999-2000 and 24% over the budgeted outlay. The district Plan for 2000-2001 has been fixed at Rs.962.36 crores. This represents an increase of 21.5% over the district plan outlay for 1999-2000. The outlay for externally aided projects in 2000-2001 is Rs.754.45 crores. Under the Special Component Plan Rs.445.26 crores have been earmarked for the welfare of Scheduled Castes and Rs.89.67 crores for the Scheduled Tribes under the Tribal Subplan.
Planning, Institutional Finance and Statistics and Science and Technology Department